The Violation of Leech’s Politeness Maxims and Interlocutor’s Responses in Enola Holmes 2020 Movie - Shofi Anis Fitriana; Hendi Pratama (English Education Journal, 2023)
The present study aimed at investigating the violation of politeness maxims of Leech (2014) and the interlocutor’s responses in the movie of Enola Holmes 2020. This study focuses on discussing violations of decency according to Leech and illocutionary acts where there is an action in acting an utterance and a response to what is done. The source of the data was taken from the utterances or dialogue spoken by the characters in this film, the method used is the documentation method by observing the film and then making a transcript of the conversation according to the required data then watching the video and reading the script repeatedly. A qualitative descriptive research design was used in this study. In line with that, Leech's theory of politeness maxims (2014) and illocutionary acts (1993) were used to analyze the research data. Based on the analysis, it was found 7 types of maxims, namely generosity maxim, tact maxim, approbation maxim, modesty maxim, obligation O to S maxim, agreement maxim, and sympathy maxim. Then, the interlocutor’s responses also found 4 types in this movie were Competitive, Convivial, Collaborative and Conflictive, the most appears of violation politeness maxim was Collaborative functions (33,3%), while the most least was Convivial functions (5,5%). There were lots of interlocutor’s reactions by the characters of the movie such as angry, smiling, offended, etc.